If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1 + -2w = -4 Solving -1 + -2w = -4 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -2w = -4 + 1 Combine like terms: -1 + 1 = 0 0 + -2w = -4 + 1 -2w = -4 + 1 Combine like terms: -4 + 1 = -3 -2w = -3 Divide each side by '-2'. w = 1.5 Simplifying w = 1.5
| -3-(-5-2n)-6(1-5n)=9 | | 9+8m=6m-3 | | 2x-9+6x=-3(3+5x) | | [1+3c]-18=-8 | | 9+8m=-3 | | 4-3w=8.5 | | 3y-6x=-33 | | F[x]=2x+12 | | -10w=15 | | x(x+4)=6(2) | | 9=v+6-2 | | (5x)=-18 | | (2x+20)=(3x-10) | | 3(2x+1)-5x=2(x+1)-3 | | (2x-20)=(3x-10) | | 15=12x^2+24x | | 4d+8-2d=6d-10 | | -12x+2y=x+2 | | 7xy-4xy+2xy+6xy+3xy-7xy= | | 14x-(3x-7)=40 | | f(n)=2*f(n-1) | | 3(3z+1)-8=40 | | -1440=-15(-15x-29) | | 8u-1=8 | | (6+k)+12=23 | | 3(2x-7)-4(x-1)= | | 2h+10=66 | | 2h+10=66 | | y-8+124=180 | | -41=5x+9 | | -1440=-15(-15x-21) | | 1.4a+10=17 |